Restricted gas diffusion in a unique porous medium — human lung - Woods, Jason C.; Yablonskiy, Dimitriy A.; Conradi, Mark S. (Diffusion Fundamentals, 2009)
Restricted diffusion of gas in the lung is in many ways similar to restricted diffusion in other porous media: atomic collisions with boundaries restrict the measured value, and there is a critical dependence on the time and distance scales of the measurement. The large free diffusivity of gases allows large pores (300 microns or larger) to be studied. The high signals of hyperpolarization permit rapid diffusion imaging of the gas itself, though fluorinated hydrocarbons are simple by comparison and are a potential alternative. The complicated nature of bifurcating human lung structure provides challenges in interpretation of results of restricted diffusion. At times sufficiently short, the short-time slope of D(t)/D0 can be related to the surface-to-volume ratio - an important measure of lung structure and early emphysema. During times of a few milliseconds, diffusion anisotropy is observed, and the principal components of diffusion are related to geometric parameters of individual airways within the pulmonary acinus. This permits regional invivo lung morphometry, which gives spatial information about features and airway geometry much smaller than the imaging voxel size. The extraordinarily long T1 of 3He provides the opportunity to use stimulated echoes to probe long diffusion times and distances. Preliminary evidence indicates that for distances significantly larger than a pulmonary acinus (≥ 1 cm), the measured diffusivity is severely restricted (near 0.02 cm2/s) and is dominated by diffusion through collateral routes. This implies that the longrange ADC measurement of 3He in lungs is an exquisitely sensitive measure of collateral airway paths.